Molecular Evolution and Functional Diversification of Replication Protein A1 in Plants - Aklilu, Behailu B.; Culligan, Kevin M. (Frontiers in Plant Science, 2016)
Replication protein A (RPA) is a heterotrimeric, single-stranded DNA binding complex required for eukaryotic DNA replication, repair and recombination. RPA is composed of three subunits, RPA1, RPA2 and RPA3. In contrast to single RPA subunit genes generally found in animals and yeast, plants encode multiple paralogs of RPA subunits, suggesting subfunctionalization. Genetic analysis demonstrates that five Arabidopsis thaliana RPA1 paralogs (RPA1A to RPA1E) have unique and overlapping functions in DNA replication, repair, and meiosis. We hypothesize here that RPA1 subfunctionalities will be reflected in major structural and sequence differences among the paralogs. To address this, we analyzed amino acid and nucleotide sequences of RPA1 paralogs from twenty-five complete genomes representing a wide spectrum of plants and unicellular green algae. We find here that the plant RPA1 gene family is divided into three general groups termed RPA1A, RPA1B and RPA1C, which likely arose from two progenitor groups in unicellular green algae. In the family Brassicaceae the RPA1B and RPA1C groups have further expanded to include two unique sub-functional paralogs RPA1D and RPA1E, respectively. In addition, RPA1 groups have unique domains, motifs, cis-elements, gene expression profiles, and pattern of conservation that are consistent with proposed functions in monocot and dicot species, including a novel C-terminal zinc-finger domain found only in plant RPA1C-like sequences. These results allow for improved prediction of RPA1 subunit functions in newly sequenced plant genomes, and potentially provide a unique molecular tool to improve classification of Brassicaceae species.